Determinan Status Gizi Pada Balita Di Wilayah Kerja Puskesmas Meureubo, Kabupaten Aceh Barat 2023 - nesa, Vanesa Silvia; Fera, Dian; Wintah, Wintah; Chandra Siahaan, Perry Boy; Murdani, Ihsan (Aceh Sanitation Journal, 2024)
The nutritional status of children under five is one of the world's concerns in the field of global public welfare in achieving the SDG's target. In the 2020-2024 National Medium-Term Development Plan (RPJMN), there are several main targets in efforts to improve the nutritional status of the community, namely reducing the prevalence of undernutrition (wasting) in children under five from 10.2% to 7% and the prevalence of stunting (short and very short) in children under five from 27.7% to 14%. This study aims to determine what factors are associated with the nutritional status of toddlers in the Meureubo West Aceh Health Center Working Area. This study is a quantitative study that is descriptive analytic with a cross-sectional design. This research was conducted at the Meureubo Health Center Work Area, West Aceh Regency. The population in this study were all mothers who had toddlers (1-5 years), namely 1,364 respondents. The sample was 93 respondents who were analyzed using univariate and bivariate analysis. The results of this study showed the level of maternal education (p-value = 0.298 > α 0.05), parental income (p-value = 0.922 > α 0.05), maternal employment (p-value = 0.672 > α 0.05), history of infectious disease (p-value = 0.010 < α 0.05), feeding (p-value = 0.668 > α 0.05). The associated variables were history of infectious diseases and the unresolved ones were mother's education level, parents' income, mother's occupation, and feeding. It is suggested that future researchers can make this research a scientific reference to conduct further research or conduct similar research in the future. Keywords: Determinants, Nutritional Status, Toddlers